Cultural Industry and Commercialization of the Culture as a Semi-formation Project in Modern Children's Education - Anilde Tombolato Tavares da Silva; Sinésio Ferraz Bueno (Universidade Federal de Santa Catarina, 2017)
This article aims to highlight the ways the Adornian reflection about Cultural Industry, commercialization of the culture and semi-formation by literature revision and help from the methodological theoretical background from the critical theory of the society, and, then establish a reflection about the importance in the cultural formation as a project of individual emancipation. In this way, it's considered important to think how the culture turns into a vehicle of semi-formation instead of a conductor to the emancipation in the modern children's education. Trying to make the individual see herself/himself as singular and free, but, being able to build from the commercialization of cultural goods, a blind spirit that conditions to isolation of himself/herself in the world, upon the principal of conformism.